Fire and fury : the Allied bombing of Germany, 1942 - 1945 - Hansen, Randall, 1970- 1970- (NAL Caliber, 2009)
Analyzes the Allied bombing of Germany during World War II, arguing that the American precision bombing was a more effective technique than the British focus on major population centers and resulted in fewer civilian casualties